Budaya Keagamaan Arab Melayu Seberang Kota Jambi - Ari Yuda Kusuma; Aman (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2021)
This article aims to describe the forms and values ​​in the Malay Arab religious culture Seberang of Jambi City. The ethnographic method with a realist ethnographic approach is used to describe the forms and values ​​in the Malay Arab religious culture Seberang Jambi City without any influence from observers. This article was written objectively from the results of participant observations, interviews, and literature studies conducted in the Seberang area of ​​Jambi City. The form of Arab Malay culture Across Jambi City obtained in this article is in the form of Assyura commemoration activities, Nisfu Syaban celebrations, Burdah, Nginau, Nuak Ketan, Nyukur babies, Pilgrimage to the Grave, Gambus, Zapin dance, Dana Syarah, and Hadrah dances. The values ​​contained in the Malay Arab religious culture Seberang Jambi City consist of cultural values, religious values, character values, family values ​​, and artistic values. Knowing the forms and values ​​of Malay Arab religious culture across Jambi City can make the public know about the culture that exists in Jambi Province. Keywords: Religious Culture, Arab Melayu, Seberang of Jambi City Artikel ini bertujuan untuk mendeskripsikan wujud dan nilai-nilai dalam budaya keagamaan Arab Melayu Seberang Kota Jambi. Metode etnografi dengan pendekatan etnografi realis digunakan untuk mendeskripsikan wujud dan nilai-nilai dalam budaya keagamaan Arab Melayu Seberang Kota Jambi tanpa ada pengaruh dari pengamat. Artikel ini ditulis secara objektif dari hasil observasi partisipan, wawancara dan studi literatur yang dilakukan pada kawasan Seberang Kota Jambi. Wujud budaya Arab Melayu Seberang Kota Jambi yang didapat dalam artikel ini berbentuk kegiatan peringatan Assyura, perayaaan Nisfu Syaban, Burdah, Nginau, Nuak Ketan, Nyukur bayi, Ziarah Kubur, Gambus, tari Zapin, tari Dana Syarah dan Hadrah. Nilai-nilai yang terdapat dalam budaya keagamaan Arab Melayu Seberang Kota Jambi terdiri dari nilai budaya, nilai agama, nilai karakter, nilai kekeluargaan dan nilai seni. Dengan dikenalnya wujud dan nila-nilai budaya keagamaan Arab Melayu Seberang Kota Jambi dapat membuat khalayak ramai mengetahui tentang budaya yang ada di Provinsi Jambi. Kata Kunci : Budaya Keagamaan, Arab Melayu, Seberang Kota Jambi